2015
DOI: 10.1362/146934715x14267608178721
|View full text |Cite
|
Sign up to set email alerts
|

Perceived service quality models: Are they still relevant?

Abstract: The aim of this paper is to review the concept of perceived service quality and to provide an update to the body of service quality knowledge. It consolidates the pathway of perceived service quality concept from its emergence to the research models development. It also critically reviews four characteristics of service quality as prerequisites of perceived service quality conceptualisation. The examination of six perceived service quality models is intended to identify a superior model that could be used by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 31 publications
1
27
0
3
Order By: Relevance
“…In turn, a precise consumption context leads to the emergence of salient meaning for the consumer in that context (Thompson, 1997). This forms a wider argument for future service quality models to consider the context of the specific industry to which they are applied (Polyakova and Mirza, 2015). Careful consideration of the unique characteristics shaping the sport and fitness industry, such as consumer motivations, high involvement of consumers in production of the service, perceived value of service experiences and after-use benefits for consumers, will create an improved link to a customer perspective on a service offered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, a precise consumption context leads to the emergence of salient meaning for the consumer in that context (Thompson, 1997). This forms a wider argument for future service quality models to consider the context of the specific industry to which they are applied (Polyakova and Mirza, 2015). Careful consideration of the unique characteristics shaping the sport and fitness industry, such as consumer motivations, high involvement of consumers in production of the service, perceived value of service experiences and after-use benefits for consumers, will create an improved link to a customer perspective on a service offered.…”
Section: Discussionmentioning
confidence: 99%
“…Another suggestion that comes from the service quality research is to follow servicedominant logic and explore what role consumers play in service quality co-creation (Polyakova and Mirza, 2015). Studies by Arnould and Price (1993), Kupers (1998) and Schembri and Sandberg (2011) confirmed that consumers actively co-construct the quality of their service experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different frameworks like service quality and product evaluation [17][18][19] provide useful tools to research the perceptions about public bathroom use. From the service quality literature, we consider relevant the focus on expectations about the service quality.…”
Section: Introductionmentioning
confidence: 99%
“…The three-component model developed by Rust and Oliver (1994) guided the conceptual development of this study. The model delineates three influencers of service quality: service product (i.e., what consumers get as an outcome), service delivery (i.e., how consumers get it), and service environment (Polyakova & Mirza, 2015). Because interactions are virtual in e-retail, the service delivery component is a critical part of e-service quality.…”
mentioning
confidence: 99%